Impact of Outdoor Adventure Education Programs on Long-Term Environmental Sustainability Behaviors Among Youths in Ondo State, Nigeria - Bola D.Ojo; Folusade C. Arowosafe (European Scientific Journal, ESJ, 2026)
This study examined how outdoor adventure education (OAE) programs influence the development of long-term environmental sustainability behaviors among youth in Ondo State, Nigeria. Using a descriptive survey design and questionnaire-based data collection, the research examined four key OAE contexts: amusement park, recreation, sports, and tourism. The study revealed a significant positive relationship between participation in these programs and sustainability behaviors among youths. Mean ratings across contexts ranged from 2.76 to 3.04, indicating consistent agreement. Statistical analysis further showed significant correlations between OAE context: amusement park (r = .660), recreation (r = .515), sports (r=.832), tourism (r=.703), and long-term environmental sustainability behaviors among youths (p < .05). The findings recommended that environmental education should be built into all amusement park programs for young visitors in Nigeria. Policymakers should promote a combined approach by linking parks, sports, recreation, and tourism programs to a single youth environmental education framework.